Stroll And Walk, Babble And Talk - More About Synonyms - Brian P. Cleary (USA CAROLRHODA BOOKS, 2008)
One book is never enough to explore the wide range of synonyms! The crazy and zany cats deliver loads of additional examples to illustrate the power of synonyms to make writing superb or terrific. Brian P. Clearys playful, rollicking verse and Brian Gables comical cats or felines turn traditional grammar lessons on end.
Keywords: Synonyms -- Synonyms